ELECTRONIC TEACHING TOOLS AND THEIR DIDACTIC CAPABILITIES - Hakberdiyev Bahrom Bobonazarovich (American Journals, 2024)
Automated education systems represent a complex type of machine teaching, where the learning process is entirely automated. In such an educational system, the learning process—comprising a complete course and lessons for a subject—is developed based on an educational program and carried out according to a specific scenario. Their level of complexity depends on the didactic tools integrated into the system, the tasks performed, and the goals set.Automated education systems are designed in such a way that they encompass providing new knowledge to students, reinforcing and perfecting that knowledge, forming skills and competencies, monitoring their progress, and evaluating their knowledge, all carried out according to specific programs.
Keywords: Machine teaching, machine capabilities, educational programs, educational courses, simulators, skill formation, distance learning, remote communication, automated education, connected tools.